The Roots of the Eurozone Sovereign Debt Crisis: PIGS vs Non-PIGS - Costa Fernandes, Abel L.; Mota, Paulo R. (Panoeconomicus, 2011)
The main purposes of this paper are twofold: a) to determine if there are significant differences on the determinants of public expenditures and tax revenues between the so-called PIGS and the remaining Eurozone member states; b) to uncover possible explanations for the different situations in which these countries find themselves nowadays. The paper focus on the effects of the cyclical state of the economy on those fiscal variables, and on the actual adherence to the fiscal rules imposed by the Maastricht Treaty. Based on the estimated results we conclude that the anti-cyclical reaction with respect to the unemployment rate is much stronger among non-PIGS. We also find that fiscal rules have, in general, not been followed by those two groups of countries. Moreover, PIGS, in spite of their economic frailties, have tried to emulate the fiscal behavior of their more prosperous Eurozone partners instead of executing more rigorous policies.Key words: European public finance, Fiscal policy, Fiscal rules.JEL: H2, H5, H6.